A bibliometric study of the work of Rosalind E. Franklin (1920-1958) - Li, Li; Zhang, Shu; Rousseau, Ronald (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2022)
After a short introduction to her life and work, we construct Rosalind Franklin’s citation environment in the sense of Howard White. This environment consists of four groups of authors related to Franklin: her co-authors, those cited by Franklin, those co-cited with Franklin, and those citing Franklin. We further found two of her articles that can be considered as suffering from delayed recognition. The article ends with a complete bibliography of Franklin. Although she never received the Nobel Prize, she most certainly was “of Nobel Class.”